Faktor Yang Mempengaruhi Ibu Dalam Memberikan ASI Esklusif di Kelurahan Anrong Appaka Kab. Pangkep - Mar’atussaliha Mar’atussaliha (Universitas Muhamadiyah Manado, 2020)
Exclusive breastfeeding in the world is only around 38 percent. When compared with the WHO target of reaching 50%, this figure is still far from the target. There are several factors that influence exclusive breastfeeding, namely knowledge, education, work. This has led to the assumption that breast milk cannot meet the needs of babies, working mothers whose workplaces do not have facilities to store expressed breast milk or who do not facilitate regulations for workers to express breast milk. In fact, breast milk is the best living fluid that babies really need, which contains various substances that are important for the baby's growth and development and suit their needs. So the aim of this research is to find out the factors that influence mothers in providing exclusive breastfeeding in Anrong Appaka Village, Kab. Pangkep. This research is an observational analytical study with a cross sectional approach. The research population was mothers who had babies aged 6-22 months in Anrong Appaka Village, Kab. Pangkep. The sample consisted of 32 people. This research uses a data collection tool in the form of a questionnaire. The research results show that there is a significant relationship between work, education and exclusive breastfeeding. The conclusion is that the job characteristics of the majority of respondents are not working. The majority of respondents have higher education. Bivariate test results There is a significant relationship between employment, education and exclusive breastfeeding.